Composite nanocellulose‐based hydrogels with spatially oriented degradation and retarded release of macromolecules. Issue 7 (24th March 2020) - Maestri, Cecilia Ada; Motta, Antonella; Moschini, Lorenzo; Bernkop‐Schnürch, Andreas; Baus, Randi Angela; Lecca, Paola; Scarpa, Marina
Abstract: The oral delivery of macromolecular therapeutics to the intestinal tract requires novel, robust, and controlled formulations. Here, we report on fabrication by molding of composite hydrogel cylinders made of cellulose nanocrystals (CNCs) and chitosan (Cht) and their performance as delivery vehicles. CNCs provide excellent mechanical and chemical stress resistance, whereas Cht allows scaffold degradation by enzyme digestion. The release of a representative medium size protein (bovine serum albumin) dispersed in the hydrogel is slow and shows a sigmoidal profile; meanwhile, the hydrogel scaffold degrades according to a preferred route, that is the cylinder is eroded along the vertical axis. The cup‐like, scarcely interconnected porous network, with a gradient of hardness along the cylinder axis, and the compact skin‐like layer covering the lateral wall which stayed in contact with the mold during gelification, explain the preferred erosion direction and the long‐term protein release. The possible effect of the molding process on hydrogel structure suggests that molding could be a simple and cheap way to favor surface compaction and directional scaffold degradation.